Methodological Model Of Improving Communicative Training Of Future Teacher Of Russian As A Foreign Language Based On Virtual Excursions - Babayeva Anjella Axatovna (Academia One Publishing, 2025)
The article presents a methodological model aimed at improving the communicative training of future teachers of Russian as a foreign language (RFL) through virtual excursions. This approach promotes the integration of digital technologies into the educational process, increasing the level of students' communicative competence. The goals, objectives, structure of the model and its practical significance are considered, and recommendations for the implementation of virtual excursions in teaching practice are offered.
Keywords: virtual excursions